The planar near field antenna system for underground investigation - (:unkn) unknown (My University, 2002)
Underground objects, especially mines are a serious problem for innocent people far from the hot-war. An antenna for the investigation of such objects is presented. In particular, E-shaped wire antennas are considered. Preliminary results obtained with these antennas are discussed.